2022
DOI: 10.1002/edn3.372
|View full text |Cite
|
Sign up to set email alerts
|

It's raining species: Rainwash eDNA metabarcoding as a minimally invasive method to assess tree canopy invertebrate diversity

Abstract: Forest canopies are highly diverse ecosystems, but despite several decades of intense research, there remain substantial gaps in our knowledge of their biodiversity and ecological interactions. One fundamental challenge in canopy research is the limited accessibility of the ecosystem. Consequently, previous studies have relied on the ap-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…In this study, we successfully detected eDNA of 42 additional species of which taxonomy was assigned at least to the genus level in overall 37 samples in addition to seven target species (Table S3 ) from two plant species only without harvesting any plant tissues. One study collecting rainfall under the canopies of four tree species with two replications for each species detected eDNA of 50 invertebrate species 19 . Another study collecting 56 individual flowers from seven plant species detected eDNA of 135 arthropod species in 67 families 16 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we successfully detected eDNA of 42 additional species of which taxonomy was assigned at least to the genus level in overall 37 samples in addition to seven target species (Table S3 ) from two plant species only without harvesting any plant tissues. One study collecting rainfall under the canopies of four tree species with two replications for each species detected eDNA of 50 invertebrate species 19 . Another study collecting 56 individual flowers from seven plant species detected eDNA of 135 arthropod species in 67 families 16 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to that, periodic survey using our method by rainfall is difficult at a region of low precipitation and during low precipitation periods. However, plant flow collection method using the rainfall would make a great contribution to the study of arthropods associated with tall trees, to which it is difficult to spray water to a whole plant body artificially, as Macher et al 19 demonstrated. In areas such as tropical rainforests, where rain falls regularly and tall trees are dense, using rainfall would be recommended for our method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…eDNA is typically recovered from plant surfaces by washing it off with water and filtering the wash‐off (Allen et al., 2022; Macher et al., 2023; Valentin et al., 2020). However, washes are probably limited to taxa from the surface of the plant.…”
Section: Introductionmentioning
confidence: 99%